Surgical Anatomy of the Orbit in Human Cadavers–An Endoscopic Pictorial Documentation - Maslehaty, Homajoun; Schultheiss, Saskia; Scholz, Martin; Petridis, Athanasios K. (Journal of Neurological Surgery Part B: Skull Base, 2018)
Background The aim of our study was a pictorial documentation of the anatomical structures of the orbit.Methods We performed a transmaxillary endoscopic approach in nine formalin-fixed human heads. We identified and documented the anatomy of the inferior part of the orbit.Results The first intraorbital anatomical landmark was the inferior rectus muscle, from which important structures medially and laterally could be identified. Anatomical structures and their relation to each other were documented and presented as illustrative figures.Conclusion Knowledge of the topographic anatomy of the inferior part of the orbit could be sufficiently imparted by our illustrations. The presented transmaxillary approach allowed a wide overview of the anatomical structures located in the inferior part of the orbit. Our pictorial documentation may provide neurosurgeons more safety and the opportunity to become familiar with the endoscopic anatomy.
Keywords: orbit; endoscopic anatomy; neuroanatomy; maxillary sinus